2021
DOI: 10.1097/md.0000000000024913
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid sarcoma of the pancreas

Abstract: Introduction: Myeloid sarcoma (MS) is an extramedullary mass, consisting of myeloid blasts with or without maturation, which efface the normal tissue architecture. It occurs mainly in lymph nodes, skin and soft tissue, testis, bone, peritoneum, and gastrointestinal tract, but rarely in the pancreas. Because their clinical courses, treatments, and prognoses are quite different, it is crucially important to distinguish between MS and pancreatic cancer. Patient concerns: W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…However, there are currently very few reports on the imaging findings of pancreatic MS. Pancreatic MS appears as a homogeneous slightly hypodense or isodense mass on non-contrast-enhanced CT and is prone to cystic change when the mass volume is large ( 12 , 14 , 15 ). On contrast-enhanced CT, it appears as a mild enhancement ( 4 , 8 , 9 ). There are only a few literature reports on the MRI signs of pancreatic MS, which include a slightly lower signal on T1WI, equal or slightly higher signal on T2WI, and limited diffusion on DWI ( 4 , 10 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are currently very few reports on the imaging findings of pancreatic MS. Pancreatic MS appears as a homogeneous slightly hypodense or isodense mass on non-contrast-enhanced CT and is prone to cystic change when the mass volume is large ( 12 , 14 , 15 ). On contrast-enhanced CT, it appears as a mild enhancement ( 4 , 8 , 9 ). There are only a few literature reports on the MRI signs of pancreatic MS, which include a slightly lower signal on T1WI, equal or slightly higher signal on T2WI, and limited diffusion on DWI ( 4 , 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Case reports or case series of pancreatic isolated MS published in the English language until May 1, 2023, were retrieved from the Web of Science, PubMed, and Science Direct databases. After detailed screening of each article, 13 patients in 12 articles met the inclusion criteria ( 4 15 ). Table 1 summarizes the clinical features, imaging findings, and immunohistochemistry of the 14 cases of isolated pancreatic MS (including the present case).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors also noted that orbital and paranasal MS enhanced homogenously only with intravenous contrast. 20 In a combined case report and retrospective review of pancreatic MS, Wu et al 24 used abdominal CT imaging to visualize abnormalities in the pancreatic head as well as possible metastases in the liver taking the form of mildly enhancing foci. In their review of 11 other cases of pancreatic MS in the literature, the authors reported that MS can sometimes visualize as homogeneous masses on CT imaging and noted that this may aid in differentiating MS from pancreatic cancer, which usually presents as a hypodense mass.…”
Section: Computed Tomographymentioning
confidence: 99%
“…In their review of 11 other cases of pancreatic MS in the literature, the authors reported that MS can sometimes visualize as homogeneous masses on CT imaging and noted that this may aid in differentiating MS from pancreatic cancer, which usually presents as a hypodense mass. 24…”
Section: Computed Tomographymentioning
confidence: 99%
“…Misdiagnosis is inevitable if we rely only on imaging. [9] Surgery with systemic chemotherapy can achieve complete remission according to recent reports. [10] We report a patient with isolated MS of the pancreas, aiming to provide the experience for the diagnose and treatment of MS. We emphasize the importance of preoperative histopathological examination.…”
Section: Case Reportmentioning
confidence: 99%